Pemberdayaan Ekonomi Masyarakat melalui Pelatihan Produk UMKM Kripik Pisang Coklat Lumer, Gabin Fla Susu, dan Spray Anti Nyamuk di Desa Cot Trap, Aceh Jaya - Vila Handayani; Titi Yuni Sartika; Zulfikar Zulfikar; Fajriati Fajriati; Hayatun Nufus; Reza Wati (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Student Community Service Program (KKN) is a form of community service aimed at enhancing community capacity and self-reliance through empowerment activities. This KKN program was implemented in Cot Trap Village under the theme "Community Economic Empowerment through Training on MSME Products: Melted Chocolate Banana Chips, Milk Custard-Filled Gabin Crackers, and Mosquito Repellent Spray in Cot Trap Village, Aceh Jaya." The activities aimed to improve the community's knowledge, skills, and motivation in transforming local resources into value-added products, while also fostering the growth of village-based micro-enterprises. The challenges faced by the community included limited skills in processing local resources into economically valuable products and a lack of innovation in home-based business development. The implementation methods included observation, identification of community needs, outreach, training, hands-on practice, mentoring, and evaluation through participant observation and assessment of the produced goods. Training focused on producing melted chocolate banana chips and milk custard-filled gabin crackers as innovative food products, as well as mosquito repellent spray as a household product with practical utility and business potential. The results demonstrated that participants were able to understand the production stages, carry out the production process independently, and create products that were more appealing and possessed added economic value. Beyond enhancing knowledge and skills, the activity fostered entrepreneurial motivation, creativity, and innovation among the community in utilizing local potential. The mentoring provided supported the sustainable development of MSME products in Cot Trap Village. Thus, the KKN program contributed to enhancing community capacity through skill and product development based on local potential, thereby supporting community economic empowerment.